Analisis Konsep Transaksi Cryptocurrency dalam Perspektif Hukum Ekonomi Syariah - Sasra, Adelia Dara; B, Baidhowi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The emergence of cryptocurrencies as a new financial instrument challenging the established financial system has been aided by advances in digital technology. By examining how well cryptocurrency transactions comply with sharia principles such as gharar, maysir, and riba, this study seeks to assess the idea from the perspective of Islamic Economic Law. A conceptual study based on literature analysis from several academic sources, rulings, and fatwas of scholars is the research methodology used. Thus, the results of the study indicate that cryptocurrencies have characteristics that raise legal questions in Islam, especially regarding their extreme volatility and speculative potential. While some scholars define them as digital assets that can be traded under certain conditions, others consider them haram because they contain elements of gharar and maysir. Therefore, to ensure that bitcoin transactions comply with the principles of Islamic Economic Law, more appropriate laws and sharia-based strategies are needed.